Halide electrolyte, preparation method thereof and electrochemical device
By combining wet grinding and microwave sintering technology to prepare halide electrolytes, the problems of unstable performance, low production efficiency and high cost in traditional methods are solved, and a more efficient and economical preparation process is achieved.
Patent Information
- Application Number
- CN202411820503.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-14
AI Technical Summary
The traditional halide electrolyte preparation method has problems such as unstable performance, low production efficiency and high cost, which limits its application in industrial production.
The halide electrolyte is prepared by combining wet grinding and microwave sintering, and finer and uniform particles are obtained through wet grinding, and microwave sintering technology is used to quickly increase the temperature and sinter it in a short time to inhibit the carbonization of organic impurities.
The performance and production efficiency of halide electrolytes are improved, while reducing the synthesis cost. The halide electrolyte particles are uniform and controllable, and have excellent performance.
Smart Images

Figure CN119627188A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solid-state batteries, and in particular to a halide electrolyte and a preparation method thereof and an electrochemical device. Background Art
[0002] Traditional liquid lithium-ion batteries have a high risk of thermal runaway, and accidents caused by lithium battery combustion and explosion occur frequently every year. Therefore, safety issues have become a bottleneck restricting the development of high-energy liquid lithium batteries. All-solid-state batteries use non-flammable, non-leaking solid electrolytes instead of organic electrolytes, which can improve the safety of lithium batteries.
[0003] As one of the key materials in all-solid-state batteries, solid electrolytes are mainly divided into polymer electrolytes, inorganic solid electrolytes and composite solid electrolytes. Among them, inorganic solid electrolytes are expected to become ideal solid electrolyte materials due to their high room temperature ionic conductivity, mechanical strength and high-voltage stability. At present, the research on inorganic solid electrolytes is mainly focused on sulfide, oxide, halide and other material systems. Among them, halide electrolytes have become one of the research hotspots due to their advantages such as high ionic conductivity, wide electrochemical window and stability of high-voltage oxide cathode materials.
[0004] However, traditional methods for preparing halide electrolytes mainly include solid-phase method, liquid-phase method, etc. These methods have certain limitations in terms of electrolyte performance, cost control, production efficiency and environmental friendliness, which restricts their application in industrial production.
[0005] Therefore, it is necessary to provide a new method for preparing halide electrolytes to improve the defects of existing preparation methods. Summary of the invention
[0006] In view of the above shortcomings of the prior art, the present invention provides a halide electrolyte and a preparation method and an electrochemical device thereof, so as to improve the problems of unstable performance and low production efficiency of the halide electrolyte prepared by the current preparation method.
[0007] To achieve the above-mentioned object and other related objects, the present invention provides a method for preparing a halide electrolyte, wherein the chemical formula of the halide electrolyte is Li 2+n Zr 1-n M n Cl 6-x-y Br x I y, wherein 0<n≤0.6; 0≤x≤6, 0≤y≤6, x+y≤6; M is a doping element, and M is selected from one or more of V, Cr, Mn, Fe, Co, and Ni. The preparation method of the halide electrolyte comprises the following steps: mixing the raw materials uniformly according to the stoichiometric ratio of the halide electrolyte chemical formula, dispersing them in a solvent for wet grinding to obtain a wet-grinded slurry; drying the wet-grinded slurry to obtain a halide precursor; and microwave sintering the halide precursor to obtain a halide electrolyte.
[0008] In one embodiment of the present invention, the Li 2+n Zr 1-n M n Cl 6-x-y Br x I y Where M is Fe, and the value range of n is 0.01≤n≤0.5.
[0009] In one embodiment of the present invention, the wet milling treatment is performed by ball milling, the rotation speed of the ball milling is 1 to 1000 rpm, and the ball milling time is 0.1 to 24 hours (h).
[0010] In one embodiment of the present invention, the sintering temperature of the microwave sintering is 100° C. to 600° C., and the sintering time is 0.1 to 24 hours.
[0011] In one embodiment of the present invention, the solvent is selected from one or more of toluene, chlorobenzene, xylene, n-hexane, glycol dimethyl ether, dibutyl ether, ethanol, 1,2-ethylenediamine, 1,2-dihalohydrin, anisole, isopropyl ether, ethyl acetate, benzyl acetate, butyl butyrate, and diisobutyl ketone.
[0012] In one embodiment of the present invention, the raw materials include a lithium source, a zirconium source, a doping source and a halogen source, the lithium source is selected from one or more of LiCl, LiBr, LiI, and Li2S; the zirconium source is selected from one or more of ZrCl4, ZrBr4, and ZrI4; the doping source is selected from one or more of halogen compounds of doping elements; the halogen source includes one or more of a chlorine source, a bromine source, and an iodine source, the chlorine source is selected from one or more of ZrCl4, LiCl, FeCl3, and FeCl2; the bromine source is selected from one or more of LiBr, ZrBr4, FeBr3, and FeBr2; the iodine source is selected from one or more of LiI, I2, ZrI4, FeI2, and FeI3.
[0013] Another aspect of the present invention provides a halide electrolyte, which is prepared by the above-mentioned preparation method.
[0014] The present invention also provides an electrochemical device, which comprises the halide electrolyte prepared by the above preparation method.
[0015] The present invention adopts a method combining wet grinding and microwave sintering to prepare halide electrolytes. The wet grinding method can obtain finer and more evenly distributed particles, while the microwave sintering technology has a fast heating rate and a short sintering time, which can effectively inhibit the carbonization of organic impurities. The wet grinding method combined with the microwave sintering technology can quickly synthesize homogeneous halide electrolytes, effectively improving the performance and production efficiency of halide electrolytes while greatly reducing the synthesis cost of halide electrolytes. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0017] Figure 1 is a flow chart of a method for preparing a halide electrolyte in one embodiment of the present invention;
[0018] Figure 2 This is the 1C / 1C cycle test curve of the lithium ion battery in Example 3 of the present invention. DETAILED DESCRIPTION
[0019] The following describes the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the following embodiments and features in the embodiments can be combined with each other without conflict.
[0020] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0021] In this article, when it comes to numerical ranges, unless otherwise specified, the distribution of optional values within the numerical range is considered continuous and includes the two numerical endpoints (i.e., the minimum value and the maximum value) of the numerical range, as well as every value between the two numerical endpoints. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be combined.
[0022] As an emerging solid electrolyte in recent years, halide electrolyte has the following advantages: high room temperature ionic conductivity, wide electrochemical window, stability to high-voltage oxide cathode materials, and the raw materials required for its synthesis are cost-effective, the synthesis process is simple, and it is easy to mass produce.
[0023] However, the current preparation methods of halide electrolytes mostly use solid-phase method and liquid-phase method. The particle size and uniformity of halide electrolyte materials prepared by solid-phase method are difficult to control, and the ball milling synthesis time is long, which may lead to unstable or decreased performance of electrolytes; the liquid-phase method takes a long time to synthesize and has poor performance; and the high-temperature sintering process has high energy consumption, long time and high cost. In addition, these traditional methods usually require a long preparation time, which limits their application in industrial production.
[0024] Based on this, the present invention provides a method for preparing a halogenated electrolyte, a halide electrolyte prepared by the preparation method, and an electrochemical device comprising the halide electrolyte. The halide electrolyte can be prepared at a lower temperature and in a shorter time by combining a wet grinding method with a microwave sintering method, and the prepared halide electrolyte particles are uniform and controllable, with excellent performance, which can greatly reduce the synthesis cost.
[0025] See also Figure 1 The present invention provides a method for preparing a halide electrolyte, the preparation method comprising the following steps:
[0026] S1, mixing the raw materials uniformly according to the stoichiometric ratio of the halide electrolyte chemical formula, dispersing them in a solvent and wet grinding them to obtain a wet grinding slurry;
[0027] S2, drying the wet-milled slurry to obtain a halide precursor;
[0028] S3. Microwave sintering the halide precursor to obtain a halide electrolyte.
[0029] The chemical formula of the halide electrolyte in step S1 is Li 2+n Zr 1-n M n Cl 6-x-y Br x I y, wherein 0<n≤0.6; 0≤x≤6, 0≤y≤6, x+y≤6; M is selected from one or more of V, Cr, Mn, Fe, Co, and Ni.
[0030] In the above formula, M represents a doping element, which can replace part of the Zr ions into the Li2ZrCl6 lattice to improve the ionic conductivity of the halide electrolyte. M can be any one of the elements listed above, for example, Fe or V or Mn, etc.; M can also be a combination of any two or more, such as Fe and Mn co-doping, or Co and Ni co-doping, etc. Preferably, M is Fe, Fe 2+ and Fe 3+ The ionic radius of Zr 4+ The ionic radius is relatively close, which means that Fe ions can effectively replace Zr ions and enter the lattice of Li2ZrCl6 without causing excessive lattice distortion; in addition, the redox potential of Fe is more matched with the electrochemical window of Li2ZrCl6 electrolyte, which can reduce the side reaction between the electrolyte and the electrode and improve the electrochemical stability. n represents the doping amount of M element, and further, 0.01≤n≤0.5, for example, n can be 0.01, 0.1, 0.3 or 0.5, etc. x represents the doping amount of Br element, and its value can be any value in the range of 0 to 6, for example, x=0, 1, 3, 5 or 6, etc.; y represents the doping amount of I element, and its value can be any value in the range of 0 to 6, for example, y=0, 2, 4 or 6, etc. It should be noted that x+y≤6, when x=0, y=0, x+y=0, the halogen element in the halide electrolyte is only Cl element; when x+y=6, the halogen element in the halide electrolyte does not contain Cl element.
[0031] The raw materials in step S1 correspond to the composition of the chemical formula of the halide electrolyte. The raw materials in the present invention include a lithium source, a zirconium source, a doping source and a halogen source, wherein the lithium source can be selected from a lithium-containing compound, and further, the lithium source is selected from one or more of LiCl, LiBr, LiI, and Li2S, for example, the lithium source is selected from LiCl, or LiBr, or a combination of LiBr and LiI, etc. The zirconium source is selected from a zirconium-containing compound, and further, the zirconium source is selected from one or more of ZrCl4, ZrBr4, and ZrI4, specifically ZrCl4, or ZrBr4, or a combination of ZrBr4 and ZrI4, etc. The doping source is selected from one or more of the halogen compounds of M, that is, the doping source varies with the type of M in the halide electrolyte, for example, if M is Fe, the doping source can be one or more combinations of FeCl3, FeBr3, or FeI3; for example, if M is Ni, the doping source can be one or more combinations of NiCl3, NiBr3, or NiI3, etc. The halogen source includes one or more of a chlorine source, a bromine source, and an iodine source. When the halide electrolyte contains only one halogen, such as Cl element, the halogen source is selected to contain a halogen source of the corresponding halogen, such as a chlorine source; when the halide electrolyte contains two halogens, such as Cl and Br elements, the halogen source is selected to contain two halogen sources of the corresponding halogen, such as a chlorine source and a bromine source; when the halide electrolyte contains three halogens, Cl, Br, and I elements, the halogen source is selected to contain a chlorine source, a bromine source, and an iodine source. Specifically, the chlorine source is selected from one or more of ZrCl4, LiCl, FeCl3, FeCl2, such as ZrCl4 or LiCl or a combination of FeCl3 and FeCl2; the bromine source is selected from one or more of LiBr, ZrBr4, FeBr3, FeBr2, such as LiBr or ZrBr4 or a combination of ZrBr4 and FeBr3; the iodine source is selected from one or more of LiI, I2, ZrI4, FeI2, FeI3, such as LiI or ZrI4 or a combination of LiI, I2 and FeI3, etc.
[0032] The wet grinding treatment in step S1 is to pre-treat the raw materials by wet ball milling to obtain fine particles with uniform particle size. Specifically, after the raw materials are mixed evenly according to the stoichiometric ratio, they are added into a ball mill, and then a certain amount of solvent is added for wet grinding to obtain a wet grinding slurry. During ball milling, the ball-to-material ratio and the amount of solvent added will affect the effect of wet ball milling. The larger the ball-to-material ratio, the higher the grinding efficiency and the finer the material particle size; the selection of the ball-to-material ratio can be determined according to the properties of the raw materials and the process requirements. For harder raw materials, a higher ball-to-material ratio can be selected to improve the grinding effect; and for softer raw materials, a lower ball-to-material ratio can be selected. In one embodiment, the mass ratio of the balls in the ball mill is (1-30):1, for example, the ball-to-material ratio can be 1:1, 10:1, 20:1 or 30:1, etc. The ratio of raw materials to solvent (material-water ratio) also has a significant impact on wet grinding efficiency. If the material-water ratio is too large, the slurry is too viscous, which has a retention effect on the grinding media, slowing down its rotation speed and reducing the ball milling efficiency; if the material-water ratio is too small, the slurry is too thin, which will cause direct impact of the grinding media and increase the loss of the grinding body. In one embodiment, the mass ratio of the raw material to the solvent is 1: (1-20), for example, the mass ratio of the raw material to the solvent is 1: 1, 1: 5, 1: 10, 1: 15 or 1: 20, etc.
[0033] In one embodiment, the solvent for wet ball milling includes one or more of toluene, chlorobenzene, xylene, n-hexane, glycol dimethyl ether, dibutyl ether, ethanol, 1,2-ethylenediamine, 1,2-ethylenedihalohydrin, anisole, isopropyl ether, ethyl acetate, benzyl acetate, butyl butyrate, and diisobutyl ketone. That is, the solvent can be any one of the above solvents, or a combination of any two or more. As an example, the solvent can be toluene, or anisole, or a combination of chlorobenzene and xylene, or a combination of anisole, isopropyl ether and ethyl acetate, and so on. Preferably, the solvent is anisole. The presence of the benzene ring in the anisole molecule gives it a certain rigidity, while the ether bond provides flexibility. This structural feature may help to form a more stable ion transport path in the electrolyte, thereby improving the electrochemical performance of the halide electrolyte.
[0034] The time and speed of wet ball milling have a significant impact on the wet milling effect. The inventor found in the study that increasing the speed of the ball mill can make the particle size of the ground material smaller. However, high-speed and long-term ball milling will cause the particle size to enter a downward trend during the refinement process, and will also increase energy consumption. Similarly, extending the ball milling time will also make the particle size of the ground material smaller, and long-term ball milling will also weaken the particle size refinement effect. Therefore, by optimizing and controlling the speed and time of ball milling, the crushing process of the material being impacted and ground can be maximized, and the ball milling efficiency can be improved. In one embodiment, the wet milling time is 0.1 to 24 hours, and further, the wet milling time is 5 to 20 hours, for example, it can be 10 hours, 15 hours or 20 hours, etc. The wet milling speed is 1 to 1000 rpm, and further, the wet milling speed is 100 to 800 rpm, for example, the wet milling speed can be 300 rpm, 500 rpm or 800 rpm, etc.
[0035] Step S2 is to dry the wet-milled slurry obtained in step S1 to obtain a halide precursor with uniform particle size. The drying process in this step can adopt a conventional drying method in the art. In one embodiment, the drying process adopts a vacuum drying method, and the vacuum drying temperature is 25 to 300°C, for example, 25°C, 80°C, 100°C, 200°C or 300°C, and the drying time is 0.1 to 24h, for example, 0.1h, 5h, 15h or 24h. The temperature and time of vacuum drying can be adaptively adjusted according to the solvent content in the wet-milled slurry. If the solvent content is high, a high temperature and long time drying method can be selected. If the solvent content is low, a low temperature and short time drying method can be selected.
[0036] Step S3 is to subject the dried halogenated precursor to microwave sintering. Microwave heating technology has a fast heating rate, a short sintering time, and can effectively inhibit the carbonization of organic impurities. In some embodiments, the temperature of microwave sintering is 100°C to 600°C, for example, 100°C, 300°C, 460°C or 600°C; the sintering time is 0.1 to 24h, and further can be 5 to 20h, for example, 5h, 10h, 15h or 20h. Compared with the traditional furnace heating method, microwave sintering can greatly shorten the sintering time and reduce energy consumption.
[0037] After step S3, a halide electrolyte with uniform and controllable particles can be obtained. The halide electrolyte is assembled into a battery. Under the same conditions, at a current rate of 1C / 1C, the number of stable cycles is increased by more than 2 times.
[0038] The second aspect of the present invention provides a halide electrolyte, which is prepared by the above-mentioned preparation method of the present invention. The chemical composition of the halide electrolyte is Li 2+n Zr 1-n Mn Cl 6-x-y Br x I y , wherein 0<n≤0.6; 0≤x≤6, 0≤y≤6, x+y≤6; M is a doping element, and M is selected from one or more of V, Cr, Mn, Fe, Co, and Ni. Further, M is Fe, and 0.01≤n≤0.5.
[0039] A third aspect of the present invention provides an electrochemical device, which comprises the halide electrolyte prepared by the above preparation method of the present invention.
[0040] The electrochemical device may be any type of energy storage device, including but not limited to all-solid-state batteries and supercapacitors. The following is an introduction using an all-solid-state battery as an example.
[0041] The all-solid-state battery comprises a positive electrode sheet, a negative electrode sheet and a halide solid electrolyte membrane, wherein the halide solid electrolyte membrane is arranged between the positive electrode sheet and the negative electrode sheet.
[0042] Specifically, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector. The positive electrode active material layer includes a positive electrode active material, a halide electrolyte, a conductive agent and a binder. The positive electrode active material can be selected from one or more of lithium nickel cobalt manganese oxide (NCM), lithium nickel oxide (LNO), lithium manganese oxide (LMO), lithium nickel manganese oxide (LNMO), lithium cobalt oxide (LCO) or lithium nickel cobalt aluminum oxide (NCA). These materials can be used alone or in combination, for example, the positive electrode active material is NCM, or a combination of NCM and LNO, etc. The conductive agent includes but is not limited to one or more of graphite, graphene, carbon black, carbon fiber and carbon nanotubes, that is, the conductive agent can be selected from any one of the above materials, such as carbon black or carbon nanotubes, etc., and can also be selected from any two or more of the above-listed materials, such as a combination of graphene and carbon fiber, etc. The binder includes one or more of polyvinylidene fluoride (PVDF), carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polyvinyl pyrrolidone (PVP), polymethyl methacrylate (PMMA), polyacrylonitrile (PAN), polyacrylic acid (PAA), polyurethane, polyvinyl alcohol (PVA), sodium alginate (Alg), ethylene-propylene-diene monomer, styrene-butadiene rubber, polyvinylidene fluoride, fluororubber, β-cyclodextrin polymer (β-CDp), polypropylene emulsion (LA132), polytetrafluoroethylene (PTFE), ethylene-tetrafluoroethylene copolymer (ETFE), fluorinated ethylene-propylene copolymer (FEP), perfluoroalkoxy resin (PFA), polychlorotrifluoroethylene (PCTFE), ethylene-chlorotrifluoroethylene copolymer (ECTFE), polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer, and polyvinylidene fluoride-chlorotrifluoroethylene copolymer. The binder can be selected from any one of the materials listed above, such as polyvinylidene fluoride, or carboxymethyl cellulose, or polyvinyl pyrrolidone, etc.; the binder can also be selected from any combination of two or more of the materials listed above, such as carboxymethyl cellulose and styrene-butadiene rubber composition; or perfluoroalkoxy resin, polychlorotrifluoroethylene and ethylene-chlorotrifluoroethylene copolymer composition, etc. The ratio between the various substances in the positive electrode active material layer can be set according to the conventional ratio in the art, and is not limited here.
[0043] The negative electrode plate can be one or more of a metal lithium plate, a metal indium plate, a lithium-indium alloy plate, for example, a metal lithium plate, or a metal indium plate, etc. The negative electrode plate can also be a composite plate including a negative electrode current collector, a negative electrode active material, a halide solid electrolyte, a conductive agent, and a binder. Among them, the negative electrode active material is selected from graphite materials, silicon materials, or a composite material of graphite materials and silicon materials. Graphite materials include but are not limited to artificial graphite, natural graphite, soft carbon, hard carbon, etc.; silicon materials include silicon oxide compounds SiO x(0 < x < 2), silicon-carbon composite, silicon, etc. The negative electrode active material can be any one of graphite-based materials, such as artificial graphite; it can also be a combination of any two or more of graphite-based materials, such as a combination of artificial graphite and natural graphite; the negative electrode active material can also be any one or a combination of two or more of silicon materials, such as silicon oxide compound, or a combination of silicon-carbon composite and silicon; the negative electrode active material can also be a combination of graphite-based materials and silicon materials, such as a combination of artificial graphite and silicon oxide compound, a combination of natural graphite and silicon-carbon composite, and so on. The conductive agent is one or more of graphite, graphene, carbon black, carbon fiber, and carbon nanotube. The binder is one or more of polyvinylidene fluoride (PVDF), carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polyvinylpyrrolidone (PVP), polymethyl methacrylate (PMMA), polyacrylonitrile (PAN), polyacrylic acid (PAA), polyurethane, polyvinyl alcohol (PVA), sodium alginate (Alg), ethylene-propylene-diene monomer, styrene-butadiene rubber, polyvinylidene fluoride, fluororubber, β-cyclodextrin polymer (β-CDp), polypropylene emulsion (LA132), polytetrafluoroethylene (PTFE), ethylene-tetrafluoroethylene copolymer (ETFE), fluorinated ethylene-propylene copolymer (FEP), perfluoroalkoxy resin (PFA), polychlorotrifluoroethylene (PCTFE), ethylene-chlorotrifluoroethylene copolymer (ECTFE), polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer, polyvinylidene fluoride-chlorotrifluoroethylene copolymer. The ratio between the substances in the negative electrode active material layer can be set with reference to the conventional ratio in the art and is not limited herein.
[0044] The assembly method of the all-solid-state battery is as follows: The halide electrolyte is cold-pressed under a pressure of 300 MPa to 400 Mpa to obtain a solid electrolyte membrane. The above-mentioned positive electrode sheet, solid electrolyte membrane, and negative electrode sheet are sequentially placed and pressed and sealed to obtain an all-solid-state lithium-ion battery. Among them, the assembly process of the all-solid-state lithium-ion battery is completed in a glove box with an inert atmosphere.
[0045] Under the same conditions, the all-solid-state battery assembled with the halide electrolyte prepared by the present invention can increase the stable cycle number by more than 2 times at a current rate of 1C / 1C.
[0046] The technical solution of the present invention will be described in detail below through several specific examples and comparative examples. Unless otherwise specified, the raw materials and reagents used in the following examples are all commercially available products, or can be prepared by conventional methods in the art, and the instruments used in the examples can be commercially purchased.
[0047] Example 1
[0048] This embodiment provides a halide electrolyte and a preparation method thereof. The chemical formula of the halide electrolyte is: Li 2.35 Zr 0.65 Fe 0.35 Cl5Br 0.5 I 0.5 The preparation method of the halide electrolyte is as follows:
[0049] (1) Under an argon atmosphere, 1.35 mol LiCl, 0.5 mol LiBr, 0.5 mol LiI, 0.65 mol ZrCl4, and 0.35 mol FeCl3 raw materials were added to a ball mill, and toluene was added as a wet grinding solvent. The amount of toluene added was 10 times the total mass of the raw materials; the ball-to-material ratio in the ball mill was 20:1; then, the wet grinding was performed at a rotation speed of 100 rpm for 1 hour to obtain a wet-milled slurry;
[0050] (2) The wet-ground slurry was placed in a vacuum oven and dried at 80°C for 12 h to obtain L i2.35 Zr 0.65 Fe 0.35 Cl5Br 0.5 I 0.5 Halide electrolyte precursors;
[0051] (3) The halide electrolyte precursor was placed in a graphite crucible, and then the graphite crucible was placed in a microwave oven and microwave sintered at 460 ° C for 4 h to obtain Li 2.35 Zr 0.65 Fe 0.35 Cl5Br 0.5 I 0.5 Halide electrolytes.
[0052] The halide electrolyte Li prepared in this example 2.35 Zr 0.65 Fe 0.35 Cl5Br 0.5 I 0.5 Used in all-solid-state batteries, the composition of the battery is as follows:
[0053] Positive electrode: LiNi with a mass ratio of 69% 0.8 Co 0.1 Mn 0.1 A dry positive electrode was prepared by mixing O2, 1% conductive agent (a mixed conductive agent of Super-P and VGCF with a mass ratio of 1:1), 29% of the above halide electrolyte and 1% PTFE, and cut into discs with a diameter of 10 mm.
[0054] Negative electrode: Li-In is the negative electrode.
[0055] Solid electrolyte membrane: solid electrolyte Li 2.35Zr 0.65 Fe 0.35 Cl5Br 0.5 I 0.5 A 300 μm thick solid electrolyte membrane was obtained by cold pressing at a pressure of 350 MPa.
[0056] Lithium-ion battery assembly: The positive electrode sheet, solid electrolyte membrane and negative electrode sheet prepared above are stacked, packaged, hot-pressed and cold-pressed to assemble into an all-solid-state battery.
[0057] Example 2
[0058] The difference between this embodiment and embodiment 1 is that the solvent added during the wet grinding process is xylene.
[0059] Example 3
[0060] The difference between this embodiment and embodiment 1 is that the solvent added during the wet grinding process is anisole.
[0061] Example 4
[0062] The difference between this embodiment and embodiment 1 is that the solvent added during the wet grinding process is butyl butyrate.
[0063] Example 5
[0064] The difference between this embodiment and embodiment 3 is that the rotation speed during the wet grinding process is 1 rpm.
[0065] Example 6
[0066] The difference between this embodiment and embodiment 3 is that the rotation speed during the wet grinding process is 50 rpm.
[0067] Example 7
[0068] The difference between this embodiment and embodiment 3 is that the rotation speed during the wet grinding process is 500 rpm.
[0069] Example 8
[0070] The difference between this embodiment and embodiment 3 is that the rotation speed during the wet grinding process is 1000 rpm.
[0071] Example 9
[0072] The difference between this embodiment and embodiment 3 is that the wet grinding time is 0.1 h.
[0073] Example 10
[0074] The difference between this embodiment and embodiment 3 is that the wet grinding time is 0.5h.
[0075] Embodiment 11
[0076] The difference between this embodiment and embodiment 3 is that the wet grinding time is 5 hours.
[0077] Example 12
[0078] The difference between this embodiment and embodiment 3 is that the wet grinding time is 10 hours.
[0079] Example 13
[0080] The difference between this embodiment and embodiment 3 is that the wet grinding time is 24 hours.
[0081] Embodiment 14
[0082] The difference between this embodiment and embodiment 3 is that the microwave sintering time is 0.1 h.
[0083] Embodiment 15
[0084] The difference between this embodiment and embodiment 3 is that the microwave sintering time is 0.5 h.
[0085] Example 16
[0086] The difference between this embodiment and embodiment 3 is that the microwave sintering time is 1 hour.
[0087] Embodiment 17
[0088] The difference between this embodiment and embodiment 3 is that the microwave sintering time is 10 hours.
[0089] Embodiment 18
[0090] The difference between this embodiment and embodiment 3 is that the microwave sintering time is 24 hours.
[0091] Embodiment 19
[0092] The difference between this embodiment and embodiment 3 is that: the chemical formula of the halide electrolyte is Li 2.1 Zr 0.9 Fe 0.1 Cl5Br 0.5 I 0.5 The ratio of the raw materials in step (1) is: 1.1 mol LiCl, 0.5 mol LiBr, 0.5 mol LiI, 0.9 mol ZrCl4, 0.1 mol FeCl3.
[0093] Embodiment 20
[0094] The difference between this embodiment and embodiment 3 is that: the chemical formula of the halide electrolyte is Li 2.01 Zr 0.99 Fe 0.01Cl5Br 0.5 I 0.5 The ratio of the raw materials in step (1) is 1.01 mol LiCl, 0.5 mol LiBr, 0.5 mol LiI, 0.99 mol ZrCl4, and 0.01 mol FeCl3.
[0095] Embodiment 21
[0096] The difference between this embodiment and embodiment 3 is that: the chemical formula of the halide electrolyte is Li 2.5 Zr 0.5 Fe 0.5 Cl5Br 0.5 I 0.5 The ratio of the raw materials in step (1) is 1.5 mol LiCl, 0.5 mol LiBr, 0.5 mol LiI, 0.5 mol ZrCl4, and 0.5 mol FeCl3.
[0097] Embodiment 22
[0098] The difference between this embodiment and embodiment 3 is that: the chemical formula of the halide electrolyte is Li 2.2 Zr 0.8 Fe 0.2 Cl5Br 0.5 I 0.5 The ratio of the raw materials in step (1) is 1.2 mol LiCl, 0.5 mol LiBr, 0.5 mol LiI, 0.8 mol ZrCl4, and 0.2 mol FeCl3.
[0099] Embodiment 23
[0100] The difference between this embodiment and embodiment 3 is that: the chemical formula of the halide electrolyte is Li 2.6 Zr 0.4 Fe 0.6 Cl5Br 0.5 I 0.5 The ratio of the raw materials in step (1) is 1.6 mol LiCl, 0.5 mol LiBr, 0.5 mol LiI, 0.4 mol ZrCl4, and 0.6 mol FeCl3.
[0101] Embodiment 24
[0102] The difference between this embodiment and embodiment 3 is that the microwave sintering temperature is 100°C.
[0103] Embodiment 25
[0104] The difference between this embodiment and embodiment 3 is that the microwave sintering temperature is 600°C.
[0105] Embodiment 26
[0106] The difference between this embodiment and embodiment 3 is that: the chemical formula of the halide electrolyte is Li 2.35 Zr 0.65 Mn 0.35 Cl5Br 0.5 I 0.5 The ratio of the raw materials in step (1) is: 1.35 mol LiCl, 0.5 mol LiBr, 0.5 mol LiI, 0.65 mol ZrCl4, and 0.35 mol MnCl3.
[0107] Embodiment 27
[0108] The difference between this embodiment and embodiment 3 is that: the chemical formula of the halide electrolyte is Li 2.35 Zr 0.65 Co 0.35 Cl5Br 0.5 I 0.5 The ratio of the raw materials in step (1) is: 1.35 mol LiCl, 0.5 mol LiBr, 0.5 mol LiI, 0.65 mol ZrCl4, and 0.35 mol CoCl3.
[0109] Embodiment 28
[0110] The difference between this embodiment and embodiment 3 is that: the chemical formula of the halide electrolyte is Li 2.35 Zr 0.65 Ni 0.35 Cl5Br 0.5 I 0.5 The ratio of the raw materials in step (1) is: 1.35 mol LiCl, 0.5 mol LiBr, 0.5 mol LiI, 0.65 mol ZrCl4, and 0.35 mol NiCl3.
[0111] Embodiment 29
[0112] The difference between this embodiment and embodiment 3 is that: the chemical formula of the halide electrolyte is Li 2.35 Zr 0.65 V 0.35 Cl5Br 0.5 I 0.5 The ratio of the raw materials in step (1) is: 1.35 mol LiCl, 0.5 mol LiBr, 0.5 mol LiI, 0.65 mol ZrCl4, and 0.35 mol VCl3.
[0113] Embodiment 30
[0114] The difference between this embodiment and embodiment 3 is that: the chemical formula of the halide electrolyte is Li 2.35 Zr 0.65 Cr 0.35 Cl5Br 0.5 I 0.5 The ratio of the raw materials in step (1) is: 1.35 mol LiCl, 0.5 mol LiBr, 0.5 mol LiI, 0.65 mol ZrCl4, and 0.35 mol CrCl3.
[0115] Embodiment 31
[0116] The difference between this embodiment and embodiment 3 is that: the chemical formula of the halide electrolyte is Li 2.35 Zr 0.65 Fe 0.2 Co 0.15 Cl5Br 0.5 I 0.5 The ratio of the raw materials in step (1) is: 1.35 mol LiCl, 0.5 mol LiBr, 0.5 mol LiI, 0.65 mol ZrCl4, 0.2 mol FeCl3, and 0.15 mol CoCl3.
[0117] Embodiment 32
[0118] The difference between this embodiment and embodiment 3 is that: the chemical formula of the halide electrolyte is Li 2.35 Zr 0.65 Fe 0.35 Cl6, the ratio of each raw material in step (1) is: 2.35mol LiCl, 0.65mol ZrCl4, 0.35molFeCl3.
[0119] Embodiment 33
[0120] The difference between this embodiment and embodiment 3 is that: the chemical formula of the halide electrolyte is Li 2.35 Zr 0.65 Fe 0.35 Br6, the ratio of each raw material in step (1) is: 2.35mol LiBr, 0.65mol ZrBr4, 0.35molFeBr3.
[0121] Embodiment 34
[0122] The difference between this embodiment and embodiment 3 is that: the chemical formula of the halide electrolyte is Li 2.35 Zr 0.65 Fe 0.35I6, the ratio of the raw materials in step (1) is: 2.35 mol LiI, 0.65 mol ZrI4, 0.35 mol FeI3.
[0123] Embodiment 35
[0124] The difference between this embodiment and embodiment 3 is that: the chemical formula of the halide electrolyte is Li 2.35 Zr 0.65 Fe 0.35 Br3I3, the ratio of each raw material in step (1) is: 1.95mol LiBr, 0.4mol LiI, 0.65mol ZrI4, 0.35mol FeBr3.
[0125] Embodiment 36
[0126] The difference between this embodiment and embodiment 3 is that: the chemical formula of the halide electrolyte is Li 2.35 Zr 0.65 Fe 0.35 Cl3Br2I, the ratio of the raw materials in step (1) is: 0.4 mol LiCl, 0.95 mol LiBr, 1 mol LiI, 0.65 mol ZrCl4, 0.35 mol FeBr3.
[0127] Comparative Example 1
[0128] The difference between this comparative example and Example 3 is that the chemical formula of the halide electrolyte is Li2ZrCl5Br 0.5 I 0.5 The ratio of the raw materials in step (1) is: 1 mol LiCl, 0.5 mol LiBr, 0.5 mol LiI, 1 mol ZrCl4.
[0129] Comparative Example 2
[0130] This embodiment provides a halide electrolyte Li 2.35 Zr 0.65 Fe 0.35 Cl5Br 0.5 I 0.5 , the preparation method of the halide electrolyte is as follows:
[0131] (1) Under argon atmosphere, 1.35 mol LiCl, 0.5 mol LiBr, 0.5 mol LiI, 0.65 mol ZrCl4, and 0.35 mol FeCl3 were added into a beaker, and anisole 10 times the total mass of the raw materials was added, and stirred at 100 rpm on a magnetic stirrer for 1 h;
[0132] (2) The obtained slurry was placed in a vacuum oven and dried at 80°C for 12 h to obtain Li 2.35 Zr 0.65 Fe 0.35 Cl5Br 0.5 I 0.5 Halide electrolyte precursors;
[0133] (3) Place the halide electrolyte precursor into a graphite crucible, then place the graphite crucible in a microwave oven and sinter at 460°C for 4 h to obtain Li 2.35 Zr 0.65 Fe 0.35 Cl5Br 0.5 I 0.5 Halide electrolytes.
[0134] The assembly method of the all-solid-state battery of this embodiment refers to Example 1.
[0135] Comparative Example 3
[0136] The difference between this comparative example and Example 3 is that the sintering method is changed to muffle furnace sintering.
[0137] Comparative Example 4
[0138] The difference between this embodiment and embodiment 3 is that the microwave sintering temperature is 80°C.
[0139] Comparative Example 5
[0140] The difference between this embodiment and embodiment 3 is that the microwave sintering temperature is 700°C.
[0141] Table 1: Process parameters and cycle performance of the halide electrolyte preparation method of each embodiment and comparative example
[0142]
[0143]
[0144]
[0145]
[0146] The present invention applies the halide electrolytes prepared in Examples 1 to 36 and Comparative Examples 1 to 5 to an all-solid-state battery, and performs a cycle performance test on the all-solid-state battery at room temperature (25°C). The operating voltage range of the battery test is 1.9-3.7V, the charge and discharge rate is 1C / 1C, and the discharge capacity of the first cycle is recorded as the 1C discharge capacity. When the battery capacity reaches 80% (80% State of Health, 80% SOH) of the first cycle capacity, the test is terminated to obtain the number of cycles at room temperature. The test results are shown in Table 1, and the cycle curve of Example 3 is plotted, see Figure 2 .
[0147] It can be seen from Table 1 that in Examples 1 to 4, toluene, xylene, anisole and butyl butyrate were used as wet grinding solvents, respectively, during wet ball milling, and other preparation conditions remained the same, and the obtained halide electrolytes were used in lithium-ion batteries. The test results show that when anisole is used as the wet grinding solvent (Example 3), the cycle performance of the lithium-ion battery is the best. This is because the presence of the benzene ring in the anisole molecule gives it a certain rigidity, while the ether bond provides flexibility; this structural feature helps to form a more stable ion transport path in the halide electrolyte, thereby improving the electrochemical performance of the halide electrolyte. From Figure 2 It can be seen that the specific capacity (the amount of electricity that can be discharged per unit mass of the battery or active material) of the battery in Example 3 decreases during the cycle, but the decrease is not large. When the cycle reaches 400 cycles, the specific capacity still reaches 150 mAh g -1 During the cycle, the coulombic efficiency (CE; the ratio of the discharge capacity to the charge capacity) of the battery is almost the same, indicating that the battery capacity loss is small. The change trends of the specific capacity and coulombic efficiency both indicate that the electrochemical performance of the halide electrolyte in Example 3 is stable.
[0148] In Example 3 and Examples 5 to 8, different rotation speeds were used during wet ball milling. The test results showed that as the wet milling speed increased, the cycle performance of the lithium-ion battery first gradually increased and then gradually decreased. This is because at the same time, a low wet milling speed may lead to uneven particle size and increased lattice defects, affecting the ion transmission efficiency; while an excessively high wet milling speed may cause excessive damage to the particle structure, resulting in a decrease in material performance.
[0149] In Example 3 and Examples 9 to 13, different ball milling times were used during wet ball milling. The test results showed that as the ball milling time increased, the cycle performance of the lithium-ion battery first gradually increased and then gradually decreased. This is because at the same rotation speed, a low synthesis time may lead to uneven particle size and increased lattice defects, affecting ion transmission efficiency; while an excessively high synthesis time may cause excessive reaction between the material and the solvent, resulting in a decrease in material performance.
[0150] In Example 3 and Examples 14 to 18, different sintering times were used in microwave sintering. The test results showed that as the sintering time increased, the cycle performance of the lithium-ion battery gradually increased and then gradually stabilized. Too short a sintering time may cause incomplete crystal formation of the material, resulting in a decrease in material performance; while too long a sintering time does not improve the battery performance too much, but instead increases the synthesis cost.
[0151] In Example 3 and Examples 19 to 23, different amounts of Fe are doped in the halide electrolyte compared to Comparative Example 1. The test results show that when a certain amount of Fe is doped in the halide electrolyte, the battery cycle effect is better, and as the doping amount of Fe in the halide electrolyte increases, the cycle performance of the lithium-ion battery gradually increases. When the doping amount of Fe is n=0.35, the cycle effect is the best, and then as the doping amount of Fe increases, the battery cycle performance gradually decreases. When the doping amount of Fe is n 0.01≤n≤0.5, the battery cycle performance is better.
[0152] In Example 3, Example 24, Example 25 and Comparative Examples 4 and 5, different sintering temperatures are used during microwave sintering. From the test results, it can be seen that the microwave sintering temperature will also have a great impact on the halide electrolyte. If the sintering temperature is too low, the crystallinity of the halide electrolyte material is poor, and there are many lattice defects, which affect ion transmission; if the sintering temperature is too high, the halide material may decompose to produce new compounds or release halogen gas, reducing the purity of the material, and too high a sintering temperature may also cause the lattice of the material to be distorted, affecting the crystal structure of the material, thereby reducing the ionic conductivity; in addition, too high a sintering temperature will also increase energy consumption. .
[0153] By comparing Example 3, Examples 26 to 31 and Comparative Example 1, it can be seen that when Fe, Mn, Co, Ni, V, Cr or a combination thereof is doped in the halide electrolyte, the battery cycle performance is significantly improved compared to that without addition. Among them, when Fe is added, the improvement effect is the best, because Fe 2+ and Fe 3+ The ionic radius of Zr 4+ The ionic radius of the Zr ions is relatively close. Fe ions can effectively replace Zr ions and enter the Li2ZrCl6 lattice without causing excessive lattice distortion. The ionic radius of other elements may be similar to that of Zr 4+The difference is large, resulting in an unstable lattice structure. In addition, the redox potential of Fe may be more compatible with the electrochemical window of the Li2ZrCl6 electrolyte, thereby reducing the side reactions between the electrolyte and the electrode and improving the electrochemical stability. Other elements may cause the electrolyte to decompose or form a passivation layer on the electrode surface due to the large difference in redox potential. Finally, the cost of Fe is the lowest. Therefore, Fe is preferred as the M element.
[0154] In Example 3 and Example 32 to Example 36, the doping element M in the halide electrolyte is the same, and the type and proportion of the halogen element are changed. From the test results, it can be seen that the halogen element has little effect on the performance of the electrolyte.
[0155] In Example 3 and Comparative Example 2, different stirring methods are used when synthesizing the halide electrolyte precursor. By comparing the test results, it can be seen that the battery cycle performance of Example 3 is significantly higher than that of Comparative Example 2, because it is difficult to synthesize an electrolyte material with excellent performance at a low synthesis speed and synthesis time due to the use of magnetic stirring.
[0156] Example 3 and Comparative Example 3 use different sintering methods. Example 3 uses microwave sintering, while Comparative Example 3 uses conventional muffle furnace sintering. Comparing the test results, it can be seen that the cycle performance of the battery in Example 3 far exceeds that of Comparative Example 3. This is because the heating rate and heat conduction of the muffle furnace are not as fast as those of microwave sintering. When the muffle furnace is used for sintering at a short sintering time, crystal defects are likely to occur, affecting the battery performance.
[0157] In summary, the present invention adopts a method combining wet grinding and microwave sintering to prepare halide electrolytes. The wet grinding method can obtain finer and more evenly distributed particles, while the microwave sintering technology has a fast heating rate and a short sintering time, which can effectively inhibit the carbonization of organic impurities. The wet grinding method combined with the microwave sintering technology can quickly synthesize homogeneous halide electrolytes, which can effectively improve the performance and production efficiency of halide electrolytes while greatly reducing the synthesis cost of halide electrolytes. Therefore, the present invention effectively overcomes some practical problems in the prior art and has high utilization value and use significance.
[0158] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A method for preparing a halide electrolyte, characterized in that: The chemical formula of the halide electrolyte is Li 2+ n Zr 1-n M n Cl 6-x-y Br x I y , wherein 0<n≤0.6; 0≤x≤6, 0≤y≤6, x+y≤6; M is a doping element, and M is selected from one or more of V, Cr, Mn, Fe, Co, and Ni. The preparation method of the halide electrolyte comprises the following steps: The raw materials are uniformly mixed according to the stoichiometric ratio of the halide electrolyte chemical formula, dispersed in a solvent and wet-milled to obtain a wet-milled slurry; Drying the wet-milled slurry to obtain a halide precursor; The halide precursor is subjected to microwave sintering to obtain a halide electrolyte.
2. The preparation method according to claim 1, characterized in that: The Li 2+n Zr 1-n M n Cl 6-x-y Br x I y Where M is Fe, and the value range of n is 0.01≤n≤0.
5.
3. The preparation method according to claim 1, characterized in that: The wet milling treatment adopts a ball milling method, the rotation speed of the ball milling method is 1 to 1000 rpm, and the ball milling time is 0.1 to 24 hours.
4. The preparation method according to claim 1, characterized in that: The sintering temperature of the microwave sintering is 100° C. to 600° C., and the sintering time is 0.1 to 24 hours.
5. The preparation method according to claim 1, characterized in that: The solvent is selected from one or more of toluene, chlorobenzene, xylene, n-hexane, glycol dimethyl ether, dibutyl ether, ethanol, 1,2-ethylenediamine, 1,2-ethylenedihalohydrin, anisole, isopropyl ether, ethyl acetate, benzyl acetate, butyl butyrate, and diisobutyl ketone.
6. The preparation method according to claim 1, characterized in that: The raw materials include a lithium source, a zirconium source, a doping source and a halogen source, wherein the lithium source is selected from one or more of LiCl, LiBr, LiI and Li2S; the zirconium source is selected from one or more of ZrCl4, ZrBr4 and ZrI4; the doping source is selected from one or more of halogen compounds of doping elements; the halogen source includes one or more of a chlorine source, a bromine source and an iodine source, wherein the chlorine source is selected from one or more of ZrCl4, LiCl, FeCl3 and FeCl2; the bromine source is selected from one or more of LiBr, ZrBr4, FeBr3 and FeBr2; the iodine source is selected from one or more of LiI, I2, ZrI4, FeI2 and FeI3.
7. A halide electrolyte, characterized in that The invention is prepared by the preparation method according to any one of claims 1 to 6.
8. An electrochemical device, characterized in that: A halide electrolyte prepared by the preparation method according to any one of claims 1 to 6.
Citation Information
Patent Citations
Nitrogen-doped carbon-coated europium-doped Li2ZrBr6 solid electrolyte material as well as preparation method and application thereof
CN116742110A
Halide solid electrolyte and preparation method and application thereof
CN118693336A
Solid electrolyte membrane as well as wet preparation method and application thereof
CN118825381A
Method of manufacturing cathode active material for lithi㎛ batteries
KR1020130073482A